2000
DOI: 10.1021/ie000127x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Selective Etching Method for Silicon Nitride Films on Silicon Substrates by Means of Subcritical Water

Abstract: The reaction of silicon nitride films on silicon substrates in sub- and supercritical water at temperatures between 100 and 400 °C has been studied for the first time. The etching rates for the silicon nitride films were higher than those for silicon dioxide films under the same conditions. A novel selective etching method for silicon nitride films using subcritical water has been proposed. The etching mechanism for silicon nitride films in subcritical water was studied by means of infrared spectroscopy and io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Interestingly, we found that etching also proceeds in ultrapure water (18.2 MΩ × cm) and not just in KCl buffer. Although SiN x etching in water has been reported before in the literature 28 , it required the use of sub- or super-critical water with temperatures in the 200 °C range and a pressure of 10 MPa. Our finding that the 532 nm laser produced much less SiN x thinning than the 488 nm laser at the same power suggests that the etch process is likely not temperature-activated but rather follows some form of wavelength-dependent photochemical etching.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that etching also proceeds in ultrapure water (18.2 MΩ × cm) and not just in KCl buffer. Although SiN x etching in water has been reported before in the literature 28 , it required the use of sub- or super-critical water with temperatures in the 200 °C range and a pressure of 10 MPa. Our finding that the 532 nm laser produced much less SiN x thinning than the 488 nm laser at the same power suggests that the etch process is likely not temperature-activated but rather follows some form of wavelength-dependent photochemical etching.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of the silicon nitride thinning is examined further here. Silicon nitride films are reported to react with water at high temperature and pressure to form hydrous silica [21], and this reaction is believed to be activated electrolytically with applied bias. Modules of this type tested in damp heat without bias showed similar, but much less degradation of this kind.…”
Section: Resultsmentioning
confidence: 99%
“…From the reported mechanism of Si 3 N 4 etching in H 3 PO 4 and HF solutions, it is known that nucleophilic substitution of Si 3 N 4 plays an important role in the etching of Si 3 N 4 . , In addition, it is reported that Si 3 N 4 can be removed in hot H 2 O with the addition of 20% citric acid at 80 °C or 20% tartaric acid at 90 °C, but the etching rates were as low as 0.52 and 0.73 Å/min, respectively . However, when H 2 O becomes superheated at a temperature between its boiling point (100 °C) and critical point (374 °C) under pressure, relatively higher etching rates of Si 3 N 4 were obtained. , The self-ionization of H 2 O increases in superheated water, increasing the concentration of H + and OH – in the solution. In particular, it was reported that nucleophilic attack by OH – determines the overall reaction kinetics of Si 3 N 4 etching in superheated water .…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, the Si 3 N 4 etching rate of pure superheated water is slower than that of conventional H 3 PO 4 at a given temperature . Another problem with Si 3 N 4 removal in superheated water is the damage and etching of the Si substrate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation